Risk Factors Associated with Stroke in Patients at the Hospitalization Service - Elmukhsinur, Elmukhsinur; Rosy, Alice; Kurniadi, Rizki (STIKES Adi Husada, 2025)
Stroke is a serious condition with a high risk of death and long-term disability. Hypertension is a major risk factor contributing significantly to both ischemic and hemorrhagic stroke. This study aims to identify risk factors associated with these two types of stroke. A cross-sectional design was used involving 173 hospitalized stroke patients from February 15 to July 29, 2022. Data were collected from medical records using a checklist and analyzed using univariate and bivariate methods with the Chi-square test. Independent variables included age, gender, hypertension, diabetes mellitus, and stroke type; the dependent variable was the incidence of stroke. Most patients were over 55 years old (62.8%), male (56.1%), and had hypertension (82.7%). Ischemic stroke occurred more frequently (68.2%) than hemorrhagic stroke (31.8%). Hypertension was significantly associated with stroke type (p = 0.017), whereas age (p = 0.113), gender (p = 0.545), and diabetes mellitus (p = 0.778) showed no significant association. Hypertension was the most prominent risk factor for stroke, particularly among individuals over 55. Preventive measures are essential to control hypertension. Nurses play a vital role in educating patients about the importance of maintaining healthy blood pressure and can develop stroke prevention programs based on significant risk factors. These programs may help reduce the prevalence of stroke and its impact on mortality and long-term disability.